Sīdhu (Śīdhu): The Sugar Cane “Wine” of Ancient and Early Medieval India - McHugh, James (History of Science in South Asia)

(untitled) (University of Alberta Library, 2020)
This article considers the nature of one particular drink made from sugar cane called sīdhu (usually m., also śīdhu), exploring the evidence from textual sources. Other drinks were made with sugar cane products, such as āsavas, medicinal ariṣṭas, and the drink called maireya, but I will not consider those here. As I argue, sīdhu was the basic fermented sugar cane drink, not strongly characterized by additives—“plain” sugar-wine as it were. Though in a manner typical of premodern Indic alcohol culture, even this one drink was a complex and variable affair. Rather than consider this drink in medical sources alone—important as that evidence may be—my methodology here is to examine the history of this drink in the light of a wide range of textual evidence, placing this drink in the broad context of pre-modern South Asian drinking culture.